2015
DOI: 10.1007/s12221-015-1177-4
|View full text |Cite
|
Sign up to set email alerts
|

Study regarding the virtual prototyping of garments for paraplegics

Abstract: The sitting position is very common in everyday life and therefore any garment should be comfortable in that positon. It is especially important for those who are disabled and are confined to a sitting position throughout life. These include paraplegics whose restricted movements are due to paralysis of the lower limbs and restrict them to a wheelchair. Garments for a sitting position should meet certain particular needs like the body dimensions and postures of each individual. Design considerations should pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 42 publications
0
27
0
2
Order By: Relevance
“…3D scanning and computer simulation techniques were studied for development of individualized functional garments for wheelchair users from perspective of ergonomic comfort in Some recent studies have shown that clothes for disabled users should not only be based on various design, fashion and comfort concepts, but should also consider particular medical problems [33][34][35][36][37]. The interviewing conducted in Slovenia among 58 adult respondents revealed that paraplegic wheelchair users are faced also with accompanying health problems because of their primary disease [35].…”
Section: Case Study 2: Computer Simulation Of Functional Clothes For mentioning
confidence: 99%
See 3 more Smart Citations
“…3D scanning and computer simulation techniques were studied for development of individualized functional garments for wheelchair users from perspective of ergonomic comfort in Some recent studies have shown that clothes for disabled users should not only be based on various design, fashion and comfort concepts, but should also consider particular medical problems [33][34][35][36][37]. The interviewing conducted in Slovenia among 58 adult respondents revealed that paraplegic wheelchair users are faced also with accompanying health problems because of their primary disease [35].…”
Section: Case Study 2: Computer Simulation Of Functional Clothes For mentioning
confidence: 99%
“…The hand pains (50.0%) and leg cramps (41.7%) are common health problems of paraplegics. It is well known that they are faced also with limited mobility of hands, atrophy of the leg muscles, poor blood circulation, and regulation of body temperature of lower extremities [34,38,39].…”
Section: Case Study 2: Computer Simulation Of Functional Clothes For mentioning
confidence: 99%
See 2 more Smart Citations
“…When analysing clothing construction according to individual measurements it is best to use scanned body models to gain accurate body shape on which computer 3D prototype will be joined in simulation process [6]. Similar approaches have been used in a number of other research works [7][8][9]. When using 3D flattening method for 3D construction of tight-fit clothing it is necessary to take inconsideration physical and mechanical properties of the material from which the clothing will be made.…”
Section: Introductionmentioning
confidence: 99%